Vaccination attitude among healthcare workers at the early phase of Covid-19 in Malaysia - Mahmud, Aidalina; Abdullah, Maha; Mohd Taib, Niazlin; Mohd Isa, Muhammad; Kqueen, Cheah Yoke; Azman, Liyana Amirah (Universitas Airlangga in collaboration with The Indonesian Public Health Union (PERSAKMI), 2023)
Background:Healthcare workers (HCWs) vaccination hesitancy during a pandemic can be problematic for the health system as these workers need to be fully vaccinated. Aims:This study aimed to determine the level of attitudevaccine hesitancy and its associated factors among HCW at the beginning of the COVID-19 pandemic. Methods:A cross-sectional study was conducted among randomly selected HCWs of a tertiary hospital in the state of Selangor, Malaysia, using an online questionnaire. The questions were designed to collect information on HCWs sociodemographic and health status, and attitude towards vaccination. Higher scores forthe four scales on attitude towards vaccination denote ahigher level of vaccine hesitancy.Results:Of the 380 respondents (98 response rate), the overall score depictedlow vaccine hesitancy despite the scores beingslightly higher on worrying over unforeseen future effects, and concerns about commercial profiteering. Women demonstrated a lower preference for natural immunity compared to men. Conclusion:In the context of this study, vaccine hesitancy among HCWs was low, which indicate good attitude towards vaccine. However, concerns on unforeseen future effects and commercial profiteering need to be addressed; and health education and promotion activities on the male workers in terms of preference for natural immunity need to be enhanced.Keywords: attitude, COVID-19, healthcare workers, vaccine hesitancy